Journey around the Notch: A Systematic Review on the History of ACL Reconstruction in the United States - White, Alex E.; Van Nest, Duncan; Tjoumakaris, Fotios P.; Freedman, Kevin B. (The Journal of Knee Surgery, 2020)
The evolution of anterior cruciate ligament (ACL) surgery, seemingly circular at times, informs and provides context for past and current controversies in ACL management. The purpose of this systematic review is to objectively summarize the historical course of ACL reconstruction and repair in the United States over the last 40 years. Femoral tunnel drilling and graft selection have evolved dramatically over the last few decades. An initial focus on restoring ACL anatomy was for a period sacrificed for decreased operative morbidity. However, recent developments in operative techniques aim to restore ACL anatomy while also achieving minimal operative morbidity. Despite this historically iterative process, there remains no perfect choice for the treatment of ACL tears. Continued research on ACL repair, anatomic graft placement, graft choice, and augmentation will help our patients over the next generation.
Keywords: anterior cruciate ligament; ACL surgery; sports medicine; systematic review